The role of general relativity on icy body reservoirs under the effects of an inner eccentric Jupiter - Zanardi, Macarena (2018)
Context. Recent studies have analyzed the dynamical evolution of outer small body populations under the effects of an eccentric inner massive perturber, which result from a planetary scattering event. These investigations suggest that such outer reservoirs are composed of particles on prograde and retrograde orbits, as well as particles whose orbit flips from prograde to retrograde and back again showing a coupling between the inclination i and the ascending node longitude Ω (Type-F particles). Aims. We analyze the role of the general relativity (GR) on the dynamics of outer particles under the influence of an inner eccentric Jupiter-mass planet produced by a planetary scattering event. In particular, we are interested in studying how the GR affects the dynamical evolution of the outer Type-F particles, which experience an eccentric Lidov-Kozai mechanism. Methods. To do this, we carried out N-body simulations with and without GR effects. Such a detailed comparative analysis allows us to strengthen our understanding concerning the GR and eccentric Lidov-Kozai combined effects on the dynamical evolution of outer particles. Results. When the GR is included, the extreme values of Ω are obtained for retrograde inclinations, while the minimum and maximum inclinations allowed for Type-F particles increase in comparison with that derived without GR effects. According to this, if the GR is included in the simulations, the range of prograde (retrograde) inclinations of the libration region is reduced (increased) with respect to that obtained in absence of GR. We find two new classes of particles when GR effects are included in the simulations. On the one hand, there are particles whose orbital plane flips from prograde to retrograde and back again without experiencing a coupling between i and Ω. On the other hand, retrograde particles show a strong coupling between i and Ω. We infer that GR may significantly modify the dynamical properties of the outer reservoirs that evolve under the effects of an eccentric inner perturber.